The value of gamma glutamyltransferase in predicting myocardial infarction in patients with acute coronary syndrome. (January 2018) - Valjevac, Amina; Rebic, Damir; Hamzic-Mehmedbasic, Aida; Sokolovic, Emir; Horozic, Dzan; Vanis, Nedim; Hadzovic-Dzuvo, Almira
Aim: To assess the utility of gamma-glutamyl transferase (GGT) and C-reactive protein (CRP) in predicting troponin elevation in patients with acute coronary syndrome.Patients: The total of 119 patients were divided into troponin-positive (n = 61) and troponin-negative (n = 58) patients.Results: CRP cut-off value ≥13.4 mg/l had the sensitivity of 68.1% and specificity of 62.5%, while the GGT cut-off value ≥61.5 IU/l had the sensitivity of 66.0% and specificity of 62.0% and combined use of both CRP and GGT had 71.4% sensitivity and 69.6% specificity in predicting troponin increase in acute coronary syndrome patients.Conclusion: GGT might be used as an adjuvant marker for risk assessment patients who present with chest pain and are suspected to have acute coronary syndrome.